2017
DOI: 10.18632/oncotarget.23145
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-mediated translational activation of ITGB3 in breast cancer cells enhances TGF-β signaling and malignant features in vitro and in vivo

Abstract: Breast cancer is the most prevalent malignancy in women and there is an urgent need for new therapeutic drugs targeting aggressive and metastatic subtypes, such as hormone-refractory triple-negative breast cancer (TNBC). Control of protein synthesis is vital to cell growth and tumour progression and permits increased resistance to therapy and cellular stress. Hypoxic cancer cells attain invasive and metastatic properties and chemotherapy resistance, but the regulation and role of protein synthesis in this sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 84 publications
1
36
0
Order By: Relevance
“…Additionally, the positive feedback loops that EDN1, ITGB3, and F3 share with inflammatory genes, such as IL-8, CXCL-1 (GRO-1), IL-33, CCL2, IL-6, and IL-1β, further emphasizes the significant role of this select gene set in angiogenesis. EDN1, ITGB3, and F3 have been implicated in tumor progression [70][71][72], but they have not been well studied with respect to DS. Their down-regulated expression, as shown in our DSV-iECs, also supports the potential presence of an anti-angiogenic microenvironment that may prevent solid tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the positive feedback loops that EDN1, ITGB3, and F3 share with inflammatory genes, such as IL-8, CXCL-1 (GRO-1), IL-33, CCL2, IL-6, and IL-1β, further emphasizes the significant role of this select gene set in angiogenesis. EDN1, ITGB3, and F3 have been implicated in tumor progression [70][71][72], but they have not been well studied with respect to DS. Their down-regulated expression, as shown in our DSV-iECs, also supports the potential presence of an anti-angiogenic microenvironment that may prevent solid tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was noted that the translational activation of integrin subunit β 3 (ITGB3) supports TGF-β pathways and advances malignant phenotypes, such as EMT. Thus, targeting integrins with antibodies has been attempted for cancer therapy [155,156]. A recent study of miR-483-3p indicated that this miRNA enhances the effectiveness of gefitinib by targeting ITGB3 [154] (Table 5).…”
Section: Mirnas Regulating Tgf-β Signalingmentioning
confidence: 99%
“…Additionally, TNBC cells can grow, survive, induce metabolic reprogramming and apoptosis, alter cell adhesion and motility to facilitate metastasis and resistance to chemotherapy under hypoxic conditions (Semenza, 2001; Muz et al, 2015). A study done using (MDA-MB-231) TNBC cells showed a translational activation of Integrin beta 3 (ITGB3) under hypoxia and that ITGB3 regulated malignant features, including EMT and cell migration, through the TGF-β pathway (Sesé et al, 2017). Also, hypoxia has been shown to represses the expression of many DNA repair genes including the tumor suppressor gene – BRCA1, which has the important role in preventing the formation of breast cancer (Scanlon and Glazer, 2015).…”
Section: Hypoxia Microenvironmentmentioning
confidence: 99%